1996
DOI: 10.1148/radiology.200.2.8685344
|View full text |Cite
|
Sign up to set email alerts
|

Fistula in ano: endoanal sonography versus endoanal MR imaging in classification.

Abstract: Endoanal MR imaging more accurately allows depiction and classification of fistula in ano than endoanal sonography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
109
0
11

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(126 citation statements)
references
References 0 publications
6
109
0
11
Order By: Relevance
“…We used a STIR protocol for body coil imaging, rather than a fat-suppressed T2-weightedprotocol,becausewe found that it provides better anatomic detail for classifica tion, in agreementwith other investigators [21]. In contrast,in most published work relat ing to endoanalfistula imaging, a 12-weighted protocol was used [17,18] becauseit provides the best balance between highlighting sepsis and supplying adequate anatomic detail for classification. We initially used STIR se quences with theendoanal coil but soonaban donedit because lossof anatomicdetaildueto signal falloff was unacceptable.…”
Section: Mr Imaging Of Fistula In Anosupporting
confidence: 58%
See 2 more Smart Citations
“…We used a STIR protocol for body coil imaging, rather than a fat-suppressed T2-weightedprotocol,becausewe found that it provides better anatomic detail for classifica tion, in agreementwith other investigators [21]. In contrast,in most published work relat ing to endoanalfistula imaging, a 12-weighted protocol was used [17,18] becauseit provides the best balance between highlighting sepsis and supplying adequate anatomic detail for classification. We initially used STIR se quences with theendoanal coil but soonaban donedit because lossof anatomicdetaildueto signal falloff was unacceptable.…”
Section: Mr Imaging Of Fistula In Anosupporting
confidence: 58%
“…Fistulographyis incorrect 84% of the time [5]. Endoanal sonography is unable to reveal sepsislying beyondthe focal rangeof the tram ducer [10,12,18], and CF cannot adequately reveal the sphincters or subtle infection [7,8].…”
Section: Mr Imaging Of Fistula In Anomentioning
confidence: 99%
See 1 more Smart Citation
“…According to our literature review, the accuracy of EAUS compared with surgery in the detection of the internal opening has varied between 28% and 94%, and the accuracy in the detection of the primary tract and secondary extension have been in the range of 36%-100% and 23%-92%, respectively [9][10][11][12] . Such a wide range of accuracy rates could be related to differences in the criteria used to identify the internal opening, differences in operator experience, and differences in the complexities of fistulae recruited.…”
Section: Discussionmentioning
confidence: 99%
“…Endoluminal anal coils offer higher spatial resolution than body coils [32], and their use resulted in an initial increased accuracy of classification of the primary track to up to 93% [33,34]. However, examinations performed using endoanal coils alone are limited by field of view and by patient discomfort, a result of which is often suboptimal image quality due to patient motion [35].…”
Section: Mr Imaging Techniquesmentioning
confidence: 99%